2011
DOI: 10.3168/jds.2011-4285
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antioxidant activity of bioactive peptide fractions obtained from yogurt

Abstract: In this study, physicochemical and microbiological properties of traditional and commercial yogurt samples were determined during 4 wk of storage. Proteolytic activity, which occurs during the storage period of yogurt samples, was also determined. Peptide fractions obtained from yogurts were investigated and the effect of proteolysis on peptide release during storage was determined. The antioxidant activities of peptides released from yogurt water-soluble extracts (WSE) and from HPLC fractions were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 53 publications
(62 reference statements)
3
32
0
Order By: Relevance
“…Elias et al (2008) pointed out in their review that peptides have substantially higher antioxidant activity than intact proteins. Several authors found significant activity of whey protein hydrolates and hydrolates of alpha-lactalbumin and reported higher activity than that for the reference compound Trolox (Tavares et al, 2011;S ßanlıdere Aloglu and Öner, 2011;Sadat et al, 2011).…”
Section: Oxidative Stability Of Fish Oil In Emulsions and Microcapsulmentioning
confidence: 89%
“…Elias et al (2008) pointed out in their review that peptides have substantially higher antioxidant activity than intact proteins. Several authors found significant activity of whey protein hydrolates and hydrolates of alpha-lactalbumin and reported higher activity than that for the reference compound Trolox (Tavares et al, 2011;S ßanlıdere Aloglu and Öner, 2011;Sadat et al, 2011).…”
Section: Oxidative Stability Of Fish Oil In Emulsions and Microcapsulmentioning
confidence: 89%
“…At the water-lipid interphase, the presence of peptides with high hydrophobicity at the lipid phase can facilitate the scavenging of free radicals generated in the system (Ranathunga et al, 2006). Structure-activity relationship, antioxidant properties and assessment, and potential applications of bioactive peptides have been thoroughly documented (Harnedy & FitzGerald, 2012;Samaranayaka & Li-Chan, 2011;Şanlıdere Aloglu &Öner, 2011;Zou et al, 2016). Both antioxidant and antimicrobial peptides from different proteinaceous sources are presented in Table 2.…”
Section: Production Of Bioactive Peptidesmentioning
confidence: 99%
“…The radical scavenging activity (RSA) values of yogurt significantly ( p < 0.05) increased by the addition of TPE‐loaded fibers (Table ). The antioxidant activity of yoghurt is known in the literature and depends on the ingredients used (Şanlıdere Aloğlu & Öner, ). Since tomato carotenoids have antioxidant activity because of the presence of different phytochemicals (Kalogeropoulos, Chiou, Pyriochou, Peristeraki, & Karathanos, ), TPE‐loaded fibers increased the antioxidant activity of yogurt.…”
Section: Resultsmentioning
confidence: 99%